A Case Study on Puspamara Sendirian Berhad - Abd Hamid, Abidullah (1999)
Bearish stock market, depreciation of currency, down-sizing of companies and other economic difficulties have resulted in a violence and pure challenging bussiness environment. These factors awakened the necessity of proper and organized planning and strategy for the company's current and coming survival. Puspamara Sdn Bhd, is textile company in Petaling Jaya, managing production of garments, apparel, design uniform and other product and services. The company experienced a decline in profitability with a 41% decrease from 1996. The inexistence of proper strategic goals and long-term planning were viewed to result to the instability of the company performance and future business continuity. This study was done in order to derive strategic alternatives and decisions to enable Puspamara Sdn. Bhd. to overcome the difficulties and eliminate further unsatisfactory outcome in the future especially in the globalization world. The study analyzed the external and internal environment and generic the strategic alternatives using the SWOT matrix and SPACE determinants model.